An Investigation of Equine Mesenchymal Stem Cell Characteristics from Different Harvest Sites: More Similar Than Not - Lombana, Karla G.; Goodrich, Laurie R.; Phillips, Jennifer Nikki; Kisiday, John David; Ruple-Czerniak, Audrey; McIlwraith, C. Wayne (Frontiers in Veterinary Science, 2015)
Diseases of the musculoskeletal system are a major cause of loss of use and retirement in sport horses. The use of bone marrow derived mesenchymal stem cells (BMDMSCs) for healing of traumatized tissue has gained substantial favor in clinical settings and can assist healing and tissue regeneration in orthopaedic injuries. There are two common sites of harvest of BMDMSCs, the sternum and ilium. Our objective was to determine if any differences exist in BMDMSCs acquired from the sternum and the ilium. We compared the two harvest sites in their propensity to undergo multilineage differentiation, differences in cell surface markers or gene transduction efficiencies. BMDMSCs were isolated and culture-expanded from five mL aspirates of bone marrow from sternum and ilium. The cells were then plated and cultured with appropriate differentiation medium to result in multi-lineage differentiation and cell characteristics were compared between sternal and ilial samples. Cell surface antibody expression of CD11a/18, CD34, CD44 and CD90 were evaluated using flow cytometry and gene transduction efficiencies were evaluated using GFP scAAV. There were no statistically significant differences in cell characteristics between MSCs cultured from sternum and ilium under any circumstances.